Prophylaxis with Single-Dose Doxycycline for the Prevention of Lyme Disease after an Ixodes scapularis Tick Bite - Nadelman, Robert B; Nowakowski, John; Fish, Durland; Falco, Richard C; Freeman, Katherine; McKenna, Donna; Welch, Peter; Marcus, Robert; Agüero-Rosenfeld, Maria E; Dennis, David T; Wormser, Gary P (The New England journal of medicine, 2001)
This large trial shows the efficacy of a single, prophylactic dose of doxycycline to prevent Lyme disease. Lyme disease is transmitted by the bite of an Ixodes scapularis tick and is the most common vector-borne disease in the United States. 1 This infection may be prevented by vaccination. 2 , 3 However, the vaccine's general acceptance is likely to be limited by its cost (a cost to the pharmacist of $61.25 per dose) and the need for multiple doses to achieve and maintain protection. 2 , 3 In addition, the vaccine is less than 100 percent effective and is currently approved only for persons 15 to 70 years of age. 3 Antimicrobial prophylaxis for persons with I. scapularis tick bites may be a . . .